GROWTH ANALYSIS OF SWINE PRODUCTION IN MANIPUR - M. DHANESWAR SINGH, N. MUHINDRO SINGH N. SAVINO (Indian Journal of Animal Production and Management, 2017)
The present study was carried out on pigs maintained at 4 blocks of Senapatidistrict (Manipur) considering 5 villages from each block. Twenty households from eachvillage were selected randomly leading to 400 households under the perview of presentstudy. Body weight at different ages had significantly influenced by pigs maintained atdifferent villages. Significantly higher body weights were observed in pigs maintained atdifferent villages of Purul and Mao Maram blocks than those of Kangpokpi and SaituGamphazol blocks. However, differences among 10 villages of former two blocks and againamong 10 villages of later two blocks were nonsignificant statistically. Weights at birth,weaning, 5th month and 8th months of age varied from 0.48 + 0.01 to 0.74 + 0.02, 4.57 +0.08 to 5.72 + 0.08, 9.55 + 0.22 to 11.85 + 0.19 and 29.80 + 0.80 to 30.48 + 0.33 Kg,respectively in different villages under study. It was concluded that body weight at differentages can be enhanced by better feeding and managemental practices.Key words: